Oxidation of Hydrogen Sulfide to Polysulfide and Thiosulfate by a Carbon Nanozyme Therapeutic Implications with an Emphasis on Down Syndrome - Derry, Paul J (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.